Note about Cholesterol - Planer, J. (Condensed Matter Physics, 2010)
A translation from German of the original paper by Prof. Planer in which he describes his observations of selective light reflection in monotropic cholesteric liquid crystal phase of cholesteryl chloride that he synthesized. Translation by Peter Oelschlaeger, Chemistry Department and Center for Macromolecular Modeling and Material Design and by Hector Cordova Mireles, Department of Physics, both from the California State Polytechnic University at Pomona. Translation was slightly revised by Prof. H.S. Kitzerow, Department of Chemistry from the University of Paderborn in Germany. Reproduced with the permission of Willey-VCH Verlag GmbH & Co. KGaA.